A moving target – cognitive narratology and feminism. Issue 6 (3rd July 2018) - Kukkonen, Karin
ABSTRACT: The present article develops a feminist approach to cognitive narratology on the basis of recent work in embodied cognition. Cognitive narratology does not traditionally consider gender perspectives, for a variety of reasons, none the least because the gendering of brains into 'male' and 'female' is deeply problematic. Contemporary cognitive narratology moves its point of interest however from the brain to the larger connections between brain, body and their situatedness in the world. From this new, embodied approach to cognition, we work toward a feminist dimension for cognitive narratology, drawing on issues of performativity, habitus and interpellation and highlighting the degree to which the notion of embodiment brings together both cognitive and cultural aspects of narrative. On the example of Hilary Mantel's short story 'The Assassination of Margaret Thatcher' (2014), we outline the complex ways in which narration, body images/body schemata, and metaphors interact and how these interactions can be analysed by an embodied feminist narratology that takes seriously both the embodied engagements of reading narrative and the edge within it that literature reveals.